Tests of a single phase induction motor - Hodgson, Frederick Earl; Johnson, James H. (My University, 1905)
Introduction: With the growing electrical industry there is an increasing demand for convenient, efficient and practical mans of utilizing electrical energy. The combined efforts of the designer and manufacturer have produced an electric motor to suit the various demands made upon it. The direct current and synchronous motors still hold their respective places in the conversion of electrical into mechanical energy. While these motors hold a place which, perhaps no other motor can hold, they are at the same time found unsatisfactory in many modern requirements. The question might justly be asked why these motors do not fill all the requirements of an electric motor, why is the induction motor coming into use and what are its advantages? Probably a strong point in favor of the induction motor is its adaptability to the present use of alternating current; however the synchronous motor with its characteristic faults also holds a place in this field. The shunt and series motor might also be used on alternating current; however the shunt motor has the objection that in the armature the current is in phase with the E.M.F. while the high inductance in the fields gives the current- in them about 90 degrees lag, thus throwing the armature current and field current out of phase with each other. To overcome this objection the field may be excited from a separate E.M.F. differing in phases 90 degrees from that supplied to the armature. A quarter phase machine would do this, one phase furnishing current for the armature while the other supplied the field, but this would load the two phases
Citation: Hodgson, Frederick Earl and Johnson, James H. Tests of a single phase induction motor. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Ratio of Transformation; Resistance in Armature; Heat Run; Theses